EVALUATION OF ANTI-DIABETIC ACTIVITY OF FICUS BENGALENSIS LINN IN ALLOXAN INDUCED RATS - A, Fegade Sachin; M, Siddaiah (Journal of Biomedical and Pharmaceutical Research, 2020)
The present study was aimed to evaluate the anti-diabetic activity of isolated compounds from aerial parts of Ficus bengalensis in alloxan induced diabetic rats. Diabetic wistar albino rats were treated with standard drug Glibenclamide and prepared drug extract in 150 mg/kg. Hypoglycemic effect was evaluated in these rats and the efficacy of isolated compounds was administered in alloxan induced diabetic rats. At the end of study period blood glucose level were statistically analyzed based on the results. Isolated fractions produced a significant reduction in blood glucose level when compared with non-treated diabetic rats. So the present research work was confirmed that the isolated compounds possess hypoglycemic effect significantly.Keywords: Ficus begalensis, antidiabetic, allaxon induced, Diabetes mellitus.